Outcomes and Safety of Endoscopic Tarsal Tunnel Decompression: A Systematic Review. Issue 1 (February 2014) - Gkotsoulias, Efthymios N.; Simonson, Devin C.; Roukis, Thomas S.
Open surgical decompression of the tarsal tunnel is the standard surgical approach for compression of the tibial nerve within the tarsal tunnel. Complications associated with this approach can be significant and periods of non–weight bearing are required. An alternative approach allowing for minimal soft tissue trauma and reduced time to ambulation is therefore desirable. Endoscopic tarsal tunnel decompression may provide such an alternative. The authors performed a systematic review of electronic databases and other relevant sources to identify material regarding the safety of endoscopic tarsal tunnel decompression. Only articles that included clear information concerning the safety of endoscopic tarsal tunnel decompression with a follow-up of at least 12 months were included. Three studies were identified involving 37 feet, with a weighted mean follow-up of 27 months. There were no permanent complications relating to iatrogenic nerve injury, deep infection, or prolonged wound healing problems documented despite initiating ambulation within one week of surgery. Two patients (5.6%) developed recurrence more than 2 years postoperative and one (2.7%) showed no improvement. Endoscopic tarsal tunnel decompression is a safe procedure with a low rate of recurrence or failure and allows for near-immediate ambulation. However, additional prospective investigations comparing open and endoscopic approaches to tarsal tunnel decompression are warranted. Levels of Evidence: Therapeutic, Level IV, Systematic analysis of Level IV studies